EFEKTIVITAS MODEL PEMBELAJARAN ROLE PLAYING TERHADAP PENINGKATAN MAHARAH KALAM SISWA KELAS VIII DI MTSN 2 MOJOKERTO - Sitti Robbani; Muqimah Liwais Sunnah (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2025)
Teaching Maharah Kalam often faces challenges in formal non-Pesantren educational institutions such as MTsN 2 Mojokerto. This condition makes maharah kalam learning less interesting, inactive, rigid, and ultimately boring. One important component in teaching and learning activities is the learning model. Role Playing Model is a method of mastering material through the development of students' imagination and appreciation. Based on this, this study raises the issue "How is the effectiveness of the Role Playing learning model on improving maharah kalam in class VIII students of MTsN 2 Mojokerto". This study aims to determine the effectiveness of the Role Playing learning model in improving maharah kalam. The method used is quantitative research with the type of true experiment, involving two classes, namely the experimental class and the control class to compare the results between the classes that received treatment and those that did not. The research sample was the VIII grade students of MTsN 2 Mojokerto. Data collection techniques include interviews, pre-test and post-test, and documentation. The results of data analysis using the t-test showed that the t value (7.785) was greater than the t table (1.998) at the 0.05 significance level. This shows that the Role Playing learning model has a significant effect in improving maharah kalam skills in class VIII MTsN 2 Mojokerto. In addition, the n-gain test results with an average score of 57.6% are included in the moderately effective category. Based on these findings, the null hypothesis (ho) is rejected and the alternative hypothesis (ha) is accepted.